Effect of disinfection and accelerated ageing on dimensional stability and detail reproduction of a facial silicone with nanoparticles - Pesqueira, Aldieris Alves [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Haddad, M. F. [UNESP]; Moreno, A. [UNESP] (Taylor & Francis, 2012)
The aim of the present study was to evaluate the effect of disinfection and accelerated ageing on the dimensional stability and detail reproduction of a facial silicone with different types of nanoparticle. A total of 60 specimens were fabricated with Silastic MDX 4-4210 silicone and they were divided into three groups: colourless and pigmented with nanoparticles (make-up powder and ceramic powder). Half of the specimens of each group were disinfected with Efferdent tablets and half with neutral soap for 60 days. Afterwards, all specimens were subjected to accelerated ageing. Both dimensional stability and detail reproduction tests were performed after specimen fabrication (initial period), after chemical disinfection, and after accelerated ageing periods (252, 504 and 1008 hours). The dimensional stability test was conducted using AutoCAD software, while detail reproduction was analysed using a stereoscope magnifying glass. Dimensional stability values were statistically evaluated by analysis of variance (ANOVA) followed by Tukey's test (p < 0.01). Detail reproduction results were compared using a score. Chemical disinfection and also accelerated ageing affected the dimensional stability of the facial silicone with statistically significant results. The silicone's detail reproduction was not affected by these two factors regardless of nanoparticle type, disinfection and accelerated ageing. © 2012 Informa UK, Ltd.
Keywords: Disinfection; Nanoparticle; Polymer; Accelerated ageing; AutoCAD software; Ceramic powder; Dimensional stability test; Reproduction tests; Silastic; Computer aided design; Nanoparticles; Photography; Polymers; Silicones; biomaterial; dimeticone; disinfectant agent; MDX 4 4210; MDX 4-4210; nanoparticle; silastic; chemistry; color; disinfection; materials testing; maxillofacial prosthesis; time; Biocompatible Materials; Color; Dimethylpolysiloxanes; Disinfectants; Materials Testing; Maxillofacial Prosthesis; Silicone Elastomers; Time Factors